Electrical Behavior of Probertite by Dielectric Spectroscopy - Okutan, M.; Yalcin, Z.; Icelli, O.; Ay, F.; Boncukcuoglu, R.; Artun, O.; Delipinar, D. (WALTER DE GRUYTER GMBH, 2014)
In this work of the material investigation, electrical parameters, which are real part and imaginary part of modulus, dielectric constant, dissipation factor, and conductivity, in the bulk pellet of probertite sample is presented. Electrical properties were investigated via temperature and frequency dependent dielectric spectroscopy. Real and imaginary part of dielectric parameter properties of the probertite were measured at frequencies from 100 to 15M Hz in the temperature range of 25 to 150 degrees C. Temperature dependence of the real part of the dielectric constant suggests that these compounds exhibit strong electromagnetic absorption and broadband electrical behavior.
Keywords: probertite; dielectric spectroscopy; electrical modulus; dissipation factor; boron clay; RELAXATION; MODULUS; CONDUCTIVITY; POLARIZATION; IMPEDANCE; Materials Science